ORIENTASI POLITIK MASYARAKAT ETNIS TIONGHOA KOTA PONTIANAK DALAM PENGUATAN KOMITMEN KEBANGSAAN - Dada Suhaida (Khazanah Pendidikan, 2015)
Political orientation is perception, attitude pattern, and political culture of somebody or society group to various political problem and political event and also forming structure and process the political activity of society as well as governance. The political orientation concerning knowledge storey; level, feeling, involvement, and repellent, and also assessment to obyek of power of order and authority in political system and governance which underway. Since political reform of be taken out in the year 1998, political system of Indonesia have opened the space for all citizens Indonesia to join in have politics, inclusive of for ethnical clan citizen of Tionghoa. Born the nya of Number Law 12 Year 2006, About Civic of Republic Of Indonesia and Number Law 40 Year 2008, about Abolition of Race Discrimination and Ethnical is represent the reflection from governmental comitmen to give the protection, certainty, and equality domicile in law at all of citizen to live to free from the race discrimination and ethnical. Keywords: Political Orientation, Ethnical Tionghoa, Nasionalism